Personal Branding Muslim Fashion on Tabriizhijab.idn - Assiddiq, Alif Akbar; Wahdiniwaty, R (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine how personal branding of Muslim fashion on Tabriizhijab.idn. The personal branding study used to analyze Tabriizhijab.idn's personal branding is using the guidelines that are often used is the concept of Eight Laws of Personal Branding, which is a personal branding strategy that emphasizes on the sides: specialization, leadership, personality, difference, appearance, unity, constancy, and good name. The method used in this research is a qualitative method by collecting secondary data sourced from writings and product sales posts marketed on the online shop sales platform in the shopee application and the results of an interview with one of Tabriizhijab's employees. Based on the research results, the personal branding carried out by Tabriizhijab.idn is in accordance with the concept of the Eight Laws of Personal Branding.